STRATEGI KYAI DALAM MENINGKATKAN MOTIVASI MENGHAFAL AL-QUR’AN DI PONDOK PESANTREN AN-NADHIRA KALIBEBER WONOSOBO - Lilik Ifatul Fauziyah; Abdul Majid; M. Yusuf Amin Nugroho (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2023)
The purpose of this research is first to find out the strategies used by kyai to increase the motivation of each student in memorizing the Qur'an, and secondly to find out the obstacles of students when memorizing the Qur'an. This research is descriptive qualitative research. In this research the researcher uses data collection techniques with the methods of interview, observation, and documentation. After the data is collected, it is analyzed using data reduction, presentation, and conclusions. The results showed, 1) in memorizing the Qur'an a santri can experience boredom, lazy, and saturated. For this reason, the kyai's strategy at the An -Nadhira Islamic boarding school is very influential in increasing the motivation of students in memorizing the Qur'an. Various kinds of strategies used by clerics include CBSA (How to Actively Learn Santri) which is able to influence the spirit of students in memorizing the Qur'an, then there are lectures and study of short hadiths to influence students in memorizing with real- life applications. 2) the obstacles in carrying out the strategies given by the kyai to the students are very many, especially the self-awareness and growth in the students' lazy nature which can affect the students' spiritual in memorizing the Qur'an.